Influence of Bicarbonates and Salt on the Physicochemical and Sensory Properties of Meatloaf. (12th April 2022) - Jaico, Tracy; Prabhakar, Himanshu; Adhikari, Koushik; Singh, Rakesh K.; Mohan, Anand
Abstract : The changing consumer attitude toward meat products warrants innovation. Recent years have seen a continuous rise in the consumer demand for ready-to-eat meat products that trigger innovations in the manufacture of restructured meat products. This study was designed to develop meatloaf with the intention of using the downgraded stream of trimmed meat and meat by-products, which are known to contain a higher quantity of connecting tissue that causes tenderness issues, moisture retention, mouthfeel, and perceived food quality. The physicochemical effects of sodium bicarbonate, potassium bicarbonate, and salt alone or in combination on physicochemical and sensory characteristics of cooked ground beef were investigated. The results obtained showed that cooked ground beef without salt had the lowest cooked yield. Instrumental textural and sensory analysis revealed that bicarbonate-treated meatloaf samples exhibited significantly better sensory and textural properties than the control (p   ≤ 0.05 ). Internal cooked color data revealed that meatloaf treated with sodium bicarbonate and potassium bicarbonate had a pinkish-red appearance with a significantly higher a ∗ value (p   ≤ 0.05 ). The findings provide evidence that inclusion of bicarbonates had a significant tenderizing and juiciness effects with improved sensory attributes of the meatloaf. The evidence presented clearly shows the potential of bicarbonate and salt will exert synergistic effects and improve eating quality and textural and sensorial attributes of meatloaf and other meat products.